POTENTIAL AND DEVELOPMENT EFFORTS OF ISLAMIC BOARDING SCHOOLS AT DAARUT TAUHIID ISLAMIC BOARDING SCHOOLS IN BANDUNG - Khambali, Khambali; Basri, Hasan; Suhartini, Andewi (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The purpose of writing this scientific paper is to reveal the potential and development efforts at Daarut Tauhiid Islamic Boarding School Bandung. The method used in writing this scientific work is descriptive with a qualitative approach. The results found show that the Daarut Tauhiid Islamic Boarding School is a pesantren that has potential and development efforts that are in line with its vision, mission, goals and programs. From a historical point of view, pesantren are not only synonymous with Islamic meaning, but also contain the meaning of Indonesian authenticity. In the process, pesantren functions as: Center for Islamic studies; da'wah development center; Center for religious and moral services; and the Center for the Development of Islamic Solidarity and Brotherhood Total Quality Management (TQM) implemented by Islamic boarding schools is a step forward in achieving the quality of Islamic boarding school education in accordance with customer satisfaction which ultimately boils down to the suitability between Islamic boarding school output and the times.